Reimagining Identity, Religion, and Nationalism: Exploring Polyphonic Voices in Fatima Bhutto’s The Runaways - Bariza Ashfaq; Bilal Asmat Cheema; Zohaib Bashir (Dialogue Social Science Review (DSSR), 2025)
This study analyzes Fatima Bhutto’s novel, The Runaways, within postmodernist paradigms, particularly how immigration and diasporic identity empower characters in terms of post-9/11 cultural identity. The theory of multiplicity and monologism dissent will be utilized to investigate the polyphonic nature of the novel with diverse voices representing the contentions in the context of recent socio-political settings. The present research intends to examine the intersection between the issues of identity, religion, and nationalism in the changing world. The purpose of the study is to interpret and assess how exactly The Runaways challenges certain views about the construction of identity, nationalism, and cultural displacement. The present study engages with wider debates about identity politics in contemporary Pakistani English fiction and the intersections of literature and social-political issues.